An Al-doped high voltage cathode of Na4Co3(PO4)2P2O7 enabling highly stable 4 V full sodium-ion batteries. Issue 32 (29th July 2019) - Liu, Xiaohao; Tang, Linbin; Li, Zhi; Zhang, Jianhua; Xu, Qunjie; Liu, Haimei; Wang, Yonggang; Xia, Yongyao; Cao, Yuliang; Ai, Xinping
Abstract : High voltage cathode material of Na4 Co3 (PO4 )2 P2 O7 is modified firstly by Al doping, and a constructed Al0.15-NCPP//HC full cell shows impressively high output voltages and superior cycling stability for rechargeable sodium-ion batteries. Abstract : The low energy density and the unsatisfactory cycling stability of cathode materials in sodium-ion battery systems have restricted their wider application. Here, a representative high voltage cathode of Na4 Co3 (PO4 )2 P2 O7 (NCPP) was modified through Al doping. The as-prepared Na3.85 Co2.85 Al0.15 (PO4 )2 P2 O7 (Al0.15-NCPP) can deliver a discharge capacity of 99.5 mA h g −1 at 0.5C. A superior rate capability (80.3 mA h g −1 at 20C and 73.4 mA h g −1 at 50C) as well as excellent ultralong cycling stability (96.3% capacity retention after 900 cycles at 10C and 82.7% capacity retention after 8000 cycles at 30C) can be obtained. The excellent sodium storage properties are benefited from the advantages of Al doping. Al doping not only enhances ionic conductivity, but also improves the structural stability. Al0.15-NCPP, which has outstanding electrochemical properties, has been proposed as a very attractive high voltage cathode material for sodium-ion batteries. More impressively, a full cell assembled with an Al0.15-NCPP cathode and hard carbon (HC) anode exhibits distinguished rate/cycling performances (70.6 mA h g −1 at 30C and 95% capacity retention after 200 cycles at 1C) and an extremely high output voltage of 4.36 V, thus providing a preview of its practical application. In addition, our research can be used to enhance the electrochemical properties of other polyanion-based high voltage electrode materials.